PETROGENESIS OF CARBONIFEROUS ADAKITES AND NB-ENRICHED ARC BASALTS IN THE ALATAW AREA, NORTHERN TIANSHAN RANGE (WESTERN CHINA): IMPLICATIONS FOR PHANEROZOIC CRUSTAL GROWTH IN THE CENTRAL ASIA OROGENIC BELT - Wang Q.; Zhao Z.-H.; Xu J.-F.; Bai Z.-H.; Xiong X.-L.; Dai T.-M.; Wyman D.A.; Li C.-F.; Chu Z.-Y. (My University, 2007)
Carboniferous volcanic rocks in the Alataw area, Northern Tianshan Range (Xinjiang), consist of early Carboniferous (ca. 320 Ma) adakites and Nb-enriched arc basalts and basaltic andesites (NEBs), and late Carboniferous (ca. 306-310 Ma) mainly high-K calc-alkaline andesites, dacites and rhyolites. The adakites are calc-alkaline, and characterized by high Na2O/K2O (1.52-3.32) ratios, negligible to positive Eu anomalies, strong depletion of heavy rare earth elements (e.g., Yb = 0.74-1.47 ppm) and Y (6.7-14.9 ppm), positive Sr and Ba but negative Nb and Ti anomalies, and relatively constant εNd(T) values (+ 3.4-+ 6.6) and (87Sr/86Sr)i ratios (0.7035-0.7042). Some andesitic and dacitic adakite samples exhibit high MgO contents similar to magnesian andesites. The NEBs are sodium-rich (Na2O/K2O = 2.03-8.06), and differ from the vast majority of arc basalts in their higher Nb, Zr, TiO2 and P2O5 contents and Nb/Th, Nb/La and Nb/U ratios, and minor negative to positive anomalies in Ba, Nb, Sr, Zr and Ti. They have the highest εNd(T) values (+ 6.4-+ 11.6) but varying (87Sr/86Sr)i ratios (0.7007-0.7063). The high-K calc-alkaline suite is similar to typical 'normal' arc volcanic rocks in terms of moderately fractionated rare earth abundance and distinctly negative Eu, Nb, Sr and Ti anomalies. They have εNd(T) values (+ 1.2-+ 6.4) and (87Sr/86Sr)i ratios (0.7018-0.7059). Geochemically, they are similar to coeval I-type granitoids in the Alataw area. Given the presence of early Carboniferous ophiolites in the Northern Tianshan Range, and the isotopically inappropriate compositions of Proterozoic metamorphic basement in the Alataw area, we argue that the Alataw adakites were most probably related to the melting of young subducted crust of the Northern Tianshan Ocean. The NEBs likely originated from mantle wedge peridotites metasomatized by adakites and minor slab-derived fluids. The later high-K calc alkaline suite was generated by AFC processes that acted on melts derived from a mantle wedge metasomatized by hydrous fluids. The larger range of isotopic compositions exhibited by both the NEB and high-K suite, relative to the adakites, suggests that the mantle wedge was heterogeneous prior to slab- or fluid-mediated metasomatism. Continental crustal growth of the Central Asian orogenic belt was dominated by contributions of the juvenile materials from the depleted mantle prior to 270 Ma and possibly afterwards. The results of this study suggest that other Carboniferous Nb-enriched basalts in the Tianshan Range were generated by subduction processes rather than by intraplate tectonics as previously proposed. © 2006 Elsevier B.V. All rights reserved.
Keywords: ADAKITE; CRUST GROWTH; MANTLE METASOMATISM; NB-ENRICHED BASALTS; SLAB MELTING; TIANSHAN; Proterozoic; Carboniferous; Precambrian::Proterozoic; Докембрий::Протерозой; Paleozoic::Carboniferous; Палеозой::Каменноугольная